UMP, Huawei Services Hong Kong Co., Limited improve collaboration in telecommunications and mobile application technology - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUALA LUMPUR, 4 July 2022 - Universiti Malaysia Pahang (UMP) signed a memorandum of understanding (MoU) with Huawei Services (Hong Kong) Co. Limited, which recently took place at Huawei Technologies, Intermark Kuala Lumpur.